Faktor-Faktor Yang Mempengaruhi Beralih Pekerjaan Pada Petani Karet di Desa Tanjung Mancang Kecamatan Kejuruan Muda Kabupaten Aceh Tamiang - Ika Nurtianty; M Jamil (Program Studi Agribisnis Fakultas Pertanian Universitas Samudra, 2019)
Rubber price and production was unstable and effected to farmer profit. Farmer looking for another chance which is from their rubber so farmer changes their job to others. Location chooses with purposive sampling that is Kejuruan Muda Sub-district, Aceh Tamiang district while the sample 30 farmers. The analyzed used multiple linear regression with independent variable are profit, education, farmer skill, and the dependent variable is an opportunity to change jobs. The result showed that profit and education variable effected an opportunity to change jobs, meanwhile farmer skill wasn’t